Reliability of Graphs Disclosed in Annual Reports of Central and Eastern European Banks. Issue 4 (3rd July 2016) - Laidroo, Laivi
Abstract : This article investigates the changes in the reliability of graphs disclosed in the annual reports of Central and Eastern European (CEE) commercial banks during crisis and noncrisis periods. The analysis covers thirty-three commercial banks from seven CEE countries during 2006–2013. The results reveal that, on average, one-third of the graphs disclosed by a bank violate at least one graph-construction principle and there appears to be a favorable measurement-distortion bias. In line with expectations, there are signs that the impression motivation of managers increases during crisis periods—severe graph distortions are twice as frequent, and distortions of financial indicator graphs increase.